Evaluación de las estrategias de reducción del impuesto a la renta en la empresa Colbapi S.A. de la ciudad de Babahoyo en el período 2021. - Vasconez Viteri, Bertha Briseida. (2023)
This case study focuses on the evaluation of the income tax reduction strategies implemented by COLBAPI S.A., a company based in Babahoyo, Ecuador, during the 2021 fiscal period. The problem that gives rise to this study is located in a business context where organizations legitimately and ethically seek to reduce their tax burden to improve their financial health and competitiveness in a constantly changing tax environment. COLBAPI S.A. faces the need to optimize its tax burden in an Ecuadorian tax environment characterized by changing regulations and fiscal challenges. To address this problem, three fundamental objectives were established: examine the income tax reduction strategies used by the company during 2021, determine the financial impact of these strategies on its economic results and, finally, identify areas where these strategies could be improved. and propose concrete recommendations to optimize its effectiveness and regulatory compliance. The results obtained through tax reconciliation shed light on the financial impact of the strategies implemented by COLBAPI S.A. during 2021. These strategies, focused on additional deductions, managed to significantly reduce income tax, freeing up financial resources that could be used for reinvestments or expansion of operations. However, the analysis also highlighted areas for improvement. The diversification of tax strategies, more meticulous management and documentation, and agile adaptation to regulatory changes were revealed as critical aspects to optimize the effectiveness of tax strategies in the future.